The murine 2-5A synthetase locus: three distinct transcripts from two linked genes. - Rutherford, M N (1991)
The cloning of cDNAs encoding murine 2-5A synthetase has identified three related transcripts, represented by a previously described cDNA clone, L3 and two novel cDNAs, L1 and L2. L1 contains an open reading frame coding for a protein that shows 70% conservation at the amino acid level when compared to the protein predicted to be encoded by L3. L2 recognizes an IFN-induced transcript 600-bp larger than the L3 transcript. These three cDNAs map to a cosmid, cII, containing two murine 2-5A synthetase genes, ME12 and ME5/ME8, situated in a head-to-tail orientation separated by approximately 8 kb. Southern analyses of ME12 and ME5/ME8 using L3, L1-specific and L2-specific probes indicate that these genes have a similar organization. cII was transiently and stably transfected into CV-1 cells. When treated with interferon, the transfected cells produced mature, murine 2-5A synthetase transcripts identified using L3 and L2-specific probes. Thus all transcripts present in IFN-treated mouse cells which are recognized by the available murine 2-5A synthetase cDNA probes map to an approximately 40 kb region of the mouse genome containing two 2-5A synthetase genes.